Indolenine – dibenzotetraaza[14]annulene nickel complexes as sensitizers for DYE – sensitized solar cells / Abdul Qaiyum Ramle - Abdul Qaiyum , Ramle (2018)
A new series of macrocyclic nickel complexes having indolenine and dibenzotetraaza[14]annulene (DBTAA) moieties were synthesized and tested for their application as sensitizers in dye-sensitized solar cells (DSSCs). The structures are furnished with anchoring groups of ethyl ester (8a, 8b, and 8c) or carboxylic acid (9c) on the indolenine moiety and hexyloxy (8b) or neopentyloxy (8c, 9c) groups on the DBTAA moiety. The best performance was exhibited by dye 9c, which under constant AM 1.5G solar simulation (100 mW cm-2) using I-/I3- electrolyte gave a short-circuit current Jsc = 0.43 mA cm-2, an open-circuit voltage Voc = 0.41 V and a fill factor FF = 0.528, corresponding to an overall conversion efficiency of η = 0.093%. The dyes 8c and 9c were studied by electrochemical impedance spectroscopy (EIS) and incident-photon-to-current-conversion efficiency (IPCE). This is the first investigation of anti-aromatic (4n π-electrons) macrocyclic DBTAA derivatives as sensitizers for DSSCs applications.